Penanganan kista radikuler pada gigi insisivus lateralis rahang atas dengan menggunakan kalsium hidroksida Management of a radicular cyst of upper lateral incisive by using calcium hydroxide - Nur Asmah; Moch. Richata Fadil; Endang Sukartini; Milly Armilia (Journal of Dentomaxillofacial Science, 2013)
Cyst is an enclosed cavity surrounded by epithelial cells and contains cholesterin. Radicular cysts are formed as aresult of chronic inflammation of malassez epithelium, caused by trauma or untreated pulp necrosis. In this case, a 21years-old man came to Clinic of Conservative Dentistry, Faculty of Dentistry, University of Padjadjaran, in Bandungto get dental endodontic treatment on his maxillary right lateral incisor. Patient experienced trauma after a motorcycleaccident ten years ago. Clinical examination with vitality test, percussion test, palpation test showed no complaints.Radiological examination revealed a radiolucent lesion with a clear boundary around the apical. The disorder wasdiagnosed as a radicular cyst of teeth 12. Conventional endodontic treatment performed using calcium hydroxide as aroot canal medication in eight times visiting. The outcome of the treatment was assessed by clinical and radiographicevaluation that showed a reduction of radicular cyst size. It is concluded that conventional endodontic treatment usingcalcium hydroxide as medications is an adequate root canal treatment, that was accompanied by periodic observationcould heal the radicular cysts